Intestinal Flora Dysregulation and Lung Cancer: Mechanism Analysis and Clinical Application - Liangyuan CHEN; Yiqing XIE; Chong LI (Chinese Journal of Lung Cancer, 2025)
Lung cancer is the deadliest form of cancer globally, with millions of new cases diagnosed each year. Although rapid advancements in surgical techniques, targeted therapies, and immunotherapy have significantly improved patient outcomes, the overall 5-year survival rate remains disappointingly low. Recent studies have highlighted the vital role of gut microbiota in maintaining host health and its close association with the onset and progression of lung cancer through various mechanisms. This article provides a systematic analysis of the role of gut microbiota in lung cancer, focusing on its immunomodulatory and metabolic functions, as well as its potential applications in treatment, while also exploring its prospects for clinical use.